Fala no ruído verbal e spatial release from masking: relação com envelhecimento, cognição e eletrofisiologia - Mello, Jayne Guterres De [UNIFESP] (2019)
Purpose. To analyze and compare speech-on-speech masking and spatial release from masking regarding to aging, cognition and electrophysiology. Method. Quantitative, observational and analytical study, approved by the Ethics Committee of the Federal University of São Paulo, nº 1.388.078. 44 subjects of both genders participated of the study: 21 of them aged between 21 and 35 years (young adults) and 23 aged between 60 and 79 years (elderly). They were divided into three groups: young adults (AJ), elderly without cognitive impairment (IsCC) and elderly with cognitive impairment (ICC). MoCA test was applied and scores ≥ 26 were considered without cognitive impairment and scores < 26 were considered with cognitive impairment. The speech recognition test was constructed and applied in the presence of a speech masking (FRV), that is, recognition of a target message (sentences) in the presence of a two-talker masking applied in two conditions (Colocated and Separated). In addition, cortical and cognitive evoked potentials (P1-N1-P2-N2 and P300) were investigated. Results. Regarding to the gender, 66.6% (n = 14) of young adults and 74% (n = 17) of the elderly were female; and 33.3% (n = 7) of the young adults and 26% (n = 6) of the elderly, males. Concerning cognition, 100% (n = 21) of the young adults showed no impairment. In the elderly group, 69.6% (n = 16) presented scores that indicated of cognitive impairment (ICC), while 30.4% (n = 7) presented no impairment (IsCC). In the FRV test: in the Colocated condition, the mean values were: AJ - 84.76% of correct answers; IsCC - 80.71%; and ICC - 69.37%. In the Separated condition, the mean values obtained were: AJ - 83.57% of correct answers; IsCC - 68.57%; and ICC - 64.68%. The differences between the groups were statistically significant, the worst performance was observed in ICC, followed by the IsCC and the AJ, in both conditions of the test. The cortical and cognitive potentials showed: a statistically significant difference between the groups only regarding the P2 wave, indicating a longer latency of this wave in the elderly than in adults. Regarding the amplitude, it was observed a larger amplitude of the P1 wave and smaller amplitude of the P2 and P300 waves in the elderly than in adults. When comparing the elderly with and without cognitive impairment, those with this impairment presented a larger amplitude of the P2 wave than those without impairment. It was observed that in the IsCC there was a positive relationship between the performance in the Separated condition and the latency of P300 wave, whereas in the ICC there was a negative relation between the performance in the Separated condition and the amplitude of the P2 wave. Conclusion. An influence of aging and cognition was observed on the recognition of the speech on a speech masking, but there was no spatial release from masking. It was observed a slower processing of information in the elderly during the task of auditory discrimination, as well as greater cortical activation required in the elderly during the task of sound detection, and it was not necessary much activation in the task of discrimination.